2003
DOI: 10.1046/j.1526-4610.2003.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endovascular Treatment on Headaches in Patients With Unruptured Intracranial Aneurysms

Abstract: Guglielmi detachable coil embolization of unruptured intracranial aneurysms was associated with reduction in severity of headaches in the majority of patients who had experienced preprocedural headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 21 publications
2
58
1
Order By: Relevance
“…[13][14][15] Regarding unruptured intracranial aneurysms, many previous investigations [16][17][18][19][20] have focused on the risks for rupture and hemorrhage while the aneurysms were left untreated, as well as the burden of risk that is associated with treatment modalities (surgical vs endovascular treatment) when the aneurysms are to be treated. 21,22 Several studies 6,[23][24][25] have also mentioned the effect of treatment of unruptured intracranial aneurysms on headache. However, literature specifically evaluating headache outcome after endovascular treatment of elderly patients with unruptured aneurysms is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Regarding unruptured intracranial aneurysms, many previous investigations [16][17][18][19][20] have focused on the risks for rupture and hemorrhage while the aneurysms were left untreated, as well as the burden of risk that is associated with treatment modalities (surgical vs endovascular treatment) when the aneurysms are to be treated. 21,22 Several studies 6,[23][24][25] have also mentioned the effect of treatment of unruptured intracranial aneurysms on headache. However, literature specifically evaluating headache outcome after endovascular treatment of elderly patients with unruptured aneurysms is rare.…”
Section: Discussionmentioning
confidence: 99%
“…5 The severity and frequency of headache may change in different ways, including improvement, aggravation, and new onset after endovascular treatment of intracranial aneurysms. 6 With a globally aging population, the number of elderly patients with intracranial aneurysms increases rapidly. Because of possible devastating consequences of aneurysm rupture and low morbidity and mortality rates of endovascular treatment, more and more elderly patients with unruptured intracranial aneurysms have been treated endovascularly.…”
mentioning
confidence: 99%
“…1,10,15 However, one study demonstrated that the use of stent assistance was not associated with improvement in headache symptoms in patients with pretreatment headaches or new headaches following treatment (1 of 5 patients improved). 19 The observed prevalence in the current series of migraine headaches (29%) and subsequent improvement of those headaches following stent-mediated embolization of aneurysms in 54% of those patients echoes the reports of sustained benefit in pain scores following aneurysm obliteration while demonstrating that the benefit of aneurysm embolization on headache symptoms may indeed persist in the population of patients undergoing stent assistance for treatment of their aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…77) Headache associated with the dura of the cavernous sinus or other skull base regions often improves after surgical treatment. 15,76) Coil embolization in 10 patients with large internal carotid artery aneurysms with headache or cranial nerve signs resulted in headache disappearing in all patients although Symptomatic Unruptured Cerebral Aneurysms aneurysm volume was larger than that before surgery due to the coil embolization; the improved headache may be due to reduced transmitted pulsations. 79) Recently, chronic headache was assessed after surgical treatment of unruptured cerebral aneurysms.…”
Section: Headache and Unruptured Cerebral Aneurysmsmentioning
confidence: 95%